Population diversity in ant-inspired optimization algorithms - Byrski, Aleksander; Węgrzyński, Krzysztof; Radwański, Wojciech; Starzec, Grażyna; Starzec, Mateusz; Bargiel, Monika; Urbańczyk, Aleksandra; Kisiel-Dorohinicki, Marek (Wydawnictwa AGH, 2021)
Measuring the diversity in evolutionary algorithms that work in real-value search spaces is often computationally complex, but it is feasible, however, measuring the diversity in combinatorial domains is practically impossible. Nevertheless, in this paper we propose several practical and feasible diversitymeasurement techniques that are dedicated to ant colony optimization algorithms, leveraging the fact that we can focus on a pheromone table even though an analysis of the search space is at least an NP problem where the direct outcomes of the search are expressed and can be analyzed. Besides sketching out the algorithms, we apply them to several benchmark problems and discuss their efficacy.
Computer Science
Bibliogr. s. 318-320.
Keywords: ant colony optimization; diversity measuring; exploitation and exploration balance; metaheuristics